2018
DOI: 10.1675/063.041.0309
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Pellets and Feces of African Royal Terns (Thalasseus maximus albididorsalis) Results in Different Estimates of Diet Composition

Abstract: A frequently used method to estimate diet composition is based on the identification of fish otoliths present in pellets and feces. However, whether pellets and feces provide similar unbiased estimates of the diet remains poorly understood. The diet of African Royal Terns (Thalasseus maximus albididorsalis) breeding in the Parc National du Delta du Saloum, Senegal, was studied. Prey species composition based on otoliths in freshly regurgitated pellets and a mixture of pellets and feces (excrement) accumulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…However, the number of suitable breeding sites is limited. Along the West African coast between Mauritania and Guinea, only a small number of sites are suitable for breeding but they may hold very large numbers of breeding seabirds (Veen et al, 2004(Veen et al, , 2018a(Veen et al, , 2019. The main sites from north to south are Parc National du Banc d'Arguin, Parc National de la Langue de Barbarie, Parc National du Delta du Saloum, Bijol Islands (Tanji Bird Reserve), Réserve Ornithologique de Kalissaye, Bijagós Archipélago, Bantambur (near Jeta) and Iles Alcatraz and Naufrage (Fig.…”
Section: Study Area and Bird Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the number of suitable breeding sites is limited. Along the West African coast between Mauritania and Guinea, only a small number of sites are suitable for breeding but they may hold very large numbers of breeding seabirds (Veen et al, 2004(Veen et al, , 2018a(Veen et al, , 2019. The main sites from north to south are Parc National du Banc d'Arguin, Parc National de la Langue de Barbarie, Parc National du Delta du Saloum, Bijol Islands (Tanji Bird Reserve), Réserve Ornithologique de Kalissaye, Bijagós Archipélago, Bantambur (near Jeta) and Iles Alcatraz and Naufrage (Fig.…”
Section: Study Area and Bird Speciesmentioning
confidence: 99%
“…While one of the parents breeds, the other is foraging or resting outside of the colony; the number of breeding pairs therefore corresponds directly to the number of identified individuals. In West Africa, a seabird monitoring project has been ongoing for over two decades (Veen et al, 2004(Veen et al, , 2018a(Veen et al, , 2019 in which a variety of counting methods have been employed in the main breeding areas. Several areas consist of large colonies where birds cannot realistically be individually counted and hence need to be estimated.…”
Section: Coastal Seabirds and Manual Countingmentioning
confidence: 99%
“…Because small and fragile otoliths may be more difficult to find than large ones, a possible bias is introduced due to underrepresentation of small fish. Furthermore, Veen et al (2018a) showed that small otoliths are strongly underrepresented in regurgitated pellets as compared to the faeces. The terns produce regurgitated pellets and defecate while sitting on the nest.…”
Section: Diet Analysismentioning
confidence: 99%
“…This study focuses on the diet of the West African Crested Tern Thalasseus albididorsalis (from here on WA Crested Tern) which was previously a subspecies of the Royal Tern T. maximus albididorsalis , but which has recently been given full species status based on DNA analysis (Collinson et al 2017). So far WA Crested Terns have received little attention in the literature (but see Veen et al 2003, 2018a,b, Correia et al 2019).…”
mentioning
confidence: 99%